2022
DOI: 10.1038/s41467-022-35036-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic partitioning of branched-chain amino acids-derived nitrogen supports renal cancer progression

Abstract: Metabolic reprogramming is critical for tumor initiation and progression. However, the exact impact of specific metabolic changes on cancer progression is poorly understood. Here, we integrate multimodal analyses of primary and metastatic clonally-related clear cell renal cancer cells (ccRCC) grown in physiological media to identify key stage-specific metabolic vulnerabilities. We show that a VHL loss-dependent reprogramming of branched-chain amino acid catabolism sustains the de novo biosynthesis of aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…These data are also notable with respect to the observation that primary RCC tumors commonly downregulate ASS1 expression and urea cycle activity [52][53][54][55] , implying that the amount of arginine in KIF or TIF is sufficient to support cancer cell proliferation without the requirement for de novo arginine synthesis involving ASS1 upregulation. To this point, a recent study found that metastatic kidney cells in the lung upregulated ASS1 expression due to the lower availability of arginine in the lung compared to the kidney 56 .…”
Section: Resultsmentioning
confidence: 99%
“…These data are also notable with respect to the observation that primary RCC tumors commonly downregulate ASS1 expression and urea cycle activity [52][53][54][55] , implying that the amount of arginine in KIF or TIF is sufficient to support cancer cell proliferation without the requirement for de novo arginine synthesis involving ASS1 upregulation. To this point, a recent study found that metastatic kidney cells in the lung upregulated ASS1 expression due to the lower availability of arginine in the lung compared to the kidney 56 .…”
Section: Resultsmentioning
confidence: 99%
“…We then looked for more specific connections between enzymes and the overall metabolic deregulation profiles of tumours, and we assessed if they differ between MTBE-SP3 and autoSP3 datasets. The ocEAn package allows to explore connections between metabolites and metabolic enzymes beyond their direct interactions: ocEAn provides weighted interactions for all possible metabolites and enzymes of a reduced functional genome-scale metabolic network, where weights represent relative distances between metabolites and enzymes in the reaction network (Sciacovelli et al , 2022). ocEAn was used to systematically explore metabolites upstream and downstream of metabolic enzymes, in order to determine which of those showed the most imbalanced metabolic abundance signatures between TT and NAT samples, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ASS1-silenced tumors treated with arginine deiminase to eliminate extracellular arginine acquire resistance to such therapy by reactivating ASS1 expression ( Rogers and Van Tine, 2019 ; Rogers et al, 2021 ). In another example, reactivation of arginine biosynthesis was shown to be necessary to support metastasis of clear cell renal cancers to the arginine limited lung environment, whereas arginine biosynthesis was not necessary and inactive in the arginine-replete primary tumor ( Sciacovelli et al, 2022 ). Lastly, ATF4-CEBPβ-mediated upregulation of ASS1 upon amino acid stress has been shown to allow AML cells to adapt to low levels of microenvironmental arginine ( Crump et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%